NFκB/Orai1 Facilitates Endoplasmic Reticulum Stress by Oxidative Stress in the Pathogenesis of Non-alcoholic Fatty Liver Disease - Zhang, Bingbing; Li, Ming; Zou, Ying; Guo, Han; Zhang, Bingdong; Xia, Cheng; Zhang, Hongyou; Yang, Wei; Xu, Chuang (Frontiers in Cell and Developmental Biology, 2019)
Non-esterified fatty acids (NEFAs) promote de novo lipogenesis, which caused abnormal hepatic lipid accumulation, by the NFκB–Orai1 pathway. Oxidative stress and endoplasmic reticulum (ER) stress have been recognized as key mechanisms in non-alcoholic fatty liver disease (NAFLD) pathogenesis. Whether Orai1 facilitates ER stress by oxidative stress remains unknown. The rat model of NAFLD was constructed by feeding high-fat diet (HFD). BRL-3A cells were treated with NEFAs, Orai1inhibtor BTP2, NFκB inhibitor wogonin, or small interfering Orai (siOrai) 1, respectively. The content of intracellular reduced glutathione (GSH) and malondialdehyde (MDA), indicating oxidative stress, was measured by a spectrophotometer. ER stress major proteins PERK, IRE1, ATF6, CHOP, and GRP78 were quantified using Western blot and qRT-PCR analyses. For the intracellular location of reactive oxygen species (ROS) and Orai1 were measured by Western blot and immunofluorescence, and cytosolic Ca2+ was measured by flow cytometry. As we expected, the liver of rats with NAFLD showed lipid droplets in HE and Oil Red O. The decreased GSH and increased MDA were found in rats fed with HFD. ER stress major proteins PERK, IRE1, ATF6, GRP78, and CHOP were significantly increased in the HFD group. In BRL-3A cells, GSH content dramatically decreased from 1 h, MDA content dramatically increased from 3 h, and expression levels of ER stress significantly increased from 3 h by NEFA treatment. Furthermore, cytosolic Ca2+ increased from 0.5 h by NEFAs treated in BRL-3A cells. It indicated that NEFAs increased cytosolic Ca2+ to induce oxidative stress, thus ER stress. The content of oxidative stress and ER stress proteins showed the same trends by NEFAs treated in BRL-3A cells. These effects were reversed by the Orai1 inhibitor BTP2 and the NFκB inhibitor wogonin. Moreover, siOrai1 abrogated NEFAs’ influence in BRL-3A cells. Last, ROS was found by NEFAs treated in BRL-3A cells, and NEFA treatment enhanced the nuclear localization of NF-κB p65 and ORAI1. It was considered that high NEFAs increased cytosolic Ca2+ and enhanced NFκB-dependent SOCE and its moiety protein Orai1 to decrease GSH and thus induced oxidative stress at earlier stages and furthermore tempted ER stress in the pathologic progress of NAFLD.